Neglected volar subluxation of the metacarpophalangeal joint of the thumb: A case report: Neglected volar subluxation of the metacarpophalangeal joint of the thumb - Yigit, Şeyhmus; Gürcan, Serkan (Acta Biomedica Atenei Parmensis, 2021)
We present an 30 year-old female patient with a volar subluxation of the metacarpophalangeal joint of the thumb.Dislocation of the metacarpophalangeal joint is rare ; volar subluxation is much more rare. Open reduction was performed through a dorsal incision because of the soft tissue interposition. Ultimately, doctors in the emergency department should pay attention to volar MCPJ subluxation and it is important to assess collateral ligament stability after closed reduction.